Relation between tax wedge and employment rate: The case of OECD countries - Kalaš, Branimir; Zelenović, Vera; Andrašić, Jelena (Industrija, 2023)
The paper investigates the relationship between tax wedge and employment rate in thirty-six OECD countries for the period 2000-2020. The aiml of this study is to identify how tax wedge indicators effects on employment level in these economies. The empirical research includes correlation analysis and panel regression in order to identify character and intensity of nexus among observed variables. Results of Hausman represent that RE model is an adequate for estimating the impact of tax wedge on employment rate in selected countries. The model results show negative correlation between these factors, as well as, that tax wedge indicators have negative impact on employment rate in OECD countries for the observed period.